Komposisi Guild dan Lebar Relung Burung Strata Bawah di Sipisang, Sumatera Barat - Novarino, Wilson; Mardiastuti, Ani; Prasetyo, Lilik B.; Widjakusuma, Reviany; Mulyani, Yeni A.; Kobayashi, Hiroshi; Salsabila, Anas; Jarulis, Jarulis; Janra, M. Nazri (Universitas Atma Jaya Yogyakarta, 2008)
Guild composition and niche breadth are important point on avian studies. This paper describes the guild composition and niche breadth of understorey bird in Sipisang, West Sumatra. The study was conducted since May 2002 until October 2004 for approximately 10 days each month (totally 284 days or 51.120 net.hours). Fifteen mist nets were operated on ground level separately on three locations, which made 60 m line each. Mist nets were operated from 6.00 AM until 18.00 PM, and checked every two hours. The captured birds were identified, ringed, measured, weighted, photographed and released. In total 1061 individuals were captured during the study; those birds belong to 103 Species and 28 families. Based on guild, study area was dominated by insectivore-frugivore birds (IF) both in species and individual level. Meanwhile terrestrial frugivorous (TF) became the lowest one. Insectivore-frugivore also recorded has the broadest niche breadth. The bird communities dominated by small birds, which have weight lower than 30 g.